2014
DOI: 10.1186/1475-2859-13-66
|View full text |Cite
|
Sign up to set email alerts
|

Biofertilizers function as key player in sustainable agriculture by improving soil fertility, plant tolerance and crop productivity

Abstract: Current soil management strategies are mainly dependent on inorganic chemical-based fertilizers, which caused a serious threat to human health and environment. The exploitation of beneficial microbes as a biofertilizer has become paramount importance in agriculture sector for their potential role in food safety and sustainable crop production. The eco-friendly approaches inspire a wide range of application of plant growth promoting rhizobacteria (PGPRs), endo- and ectomycorrhizal fungi, cyanobacteria and many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
466
0
22

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 902 publications
(498 citation statements)
references
References 110 publications
10
466
0
22
Order By: Relevance
“…According to several reports, PGPR might mediate plant growth promotion through the production of various substances by the alteration of the whole microbial community in rizhospere niche (de Souza, Ambrosini, & Passaglia, 2015). PGPR had direct mechanisms through facilitating nutrient uptake or increasing nutrient availability by nitrogen fixation, solubilization of nutrients, mineralization of organic compounds and production of phytohormones (Bhardwaj, Ansari, Sahoo, & Tuteja, 2014). PGPR supported plant growth also through production of siderophore (low molecular weight iron-chelating compound) (Rahmoune et al, 2017), of which the plant can take up iron in large number (Sujatha & Ammani, 2013) and phytohormone (Zahedi & Abbasi, 2015).…”
Section: Plant Growth Improvement and White Rust Incidencementioning
confidence: 99%
See 2 more Smart Citations
“…According to several reports, PGPR might mediate plant growth promotion through the production of various substances by the alteration of the whole microbial community in rizhospere niche (de Souza, Ambrosini, & Passaglia, 2015). PGPR had direct mechanisms through facilitating nutrient uptake or increasing nutrient availability by nitrogen fixation, solubilization of nutrients, mineralization of organic compounds and production of phytohormones (Bhardwaj, Ansari, Sahoo, & Tuteja, 2014). PGPR supported plant growth also through production of siderophore (low molecular weight iron-chelating compound) (Rahmoune et al, 2017), of which the plant can take up iron in large number (Sujatha & Ammani, 2013) and phytohormone (Zahedi & Abbasi, 2015).…”
Section: Plant Growth Improvement and White Rust Incidencementioning
confidence: 99%
“…As biocontrol agents, the bacterium may act through various mechanisms, regardless of their effect on the promotion of plant growth, like auxin production (Miransari & Smith, 2014), ethylene levels decrement (Liu & Zhang, 2015) or nitrogen fixation in association with roots (Reed, Cleveland, & Townsend, 2011). It is about only 1 to 2 % of bacteria promote plant growth originated from the rhizosphere (Beneduzi, Ambrosini, & Passaglia, 2012). Bacteria from wide range of genera have been identified as PGPR, of which Bacillus sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The eco-friendly approach encourages the use of PGPR to improve plant tolerance to salinity stress. 5 The beneficial PGPRs interactions in the rhizosphere decide plant health. 4 Azotobacter participates in diverse metabolic functions owing to capacity to produce vitamins and hormones themselves and promotes plant growth and development.…”
mentioning
confidence: 99%
“…This action enhances growth through the supply and availability of primary nutrients to the plant. Bhardwaj, et al, (2014) and Arora, et al, (2012) identified it role on atmospheric nitrogen fixation, mineralization of organic compounds and phytohormones synthesis. Biofertilizers are essential components of organic agriculture and are vital in maintaining long-term soil fertility and sustainability through the production of safe and healthy food.…”
Section: Biofertilizationmentioning
confidence: 99%